THE RELATIONSHIP BETWEEN MOTHERS' KNOWLEDGE, ATTITUDES AND ACTIONS REGARDING STUNTING AT THE WEST LIMBOTO PUBLIC HEALTH CENTER, GORONTALO REGENCY - Amel Zainudin; Deby Sinta Darise; Arpin Arpin (Persatuan Dosen Kesehatan Masyarakat, 2026)
Stunting is a chronic nutritional problem that remains a national concern because it has long-term impacts on children's physical growth, cognitive development, and future productivity. One of the main factors causing stunting is the low level of maternal knowledge about nutrition, parenting patterns, and appropriate preventive measures during the child's growth period. This study aims to explore the relationship between maternal knowledge, attitudes, and actions regarding stunting in the work area of the West Limboto Community Health Center, Gorontalo Regency. This study applied a quantitative method with a cross-sectional design , and data analysis was carried out using the Chi-Square test to identify relationships between the variables studied. The population in this study consisted of 72 mothers with toddlers, with a sampl e size of 42 respondents determined using the Slovin formula. The research instrument was a questionnaire that had been tested for validity and reliability, covering aspects of maternal knowledge, attitudes, and actions regarding stunting. The results of the study indicate a significant relationship between maternal knowledge and attitudes (p = 0.000 0.05), knowledge and actions (p = 0.002 0.05), and attitudes and actions (p = 0.001 0.05) in stunting prevention efforts. Mothers with good knowledge tend to show positive attitudes and implement appropriate actions in maintaining nutritional intake and child health. The conclusion of this study confirms that increasing maternal knowledge plays a crucial role in shaping attitudes and actions that support stunting prevention. Therefore, efforts are needed to educate mothers about nutrition, improve access to information, and provide ongoing support for mothers of toddlers to strengthen stunting prevention behaviors in the West Limboto Community Health Center work area.Keywords : Knowledge, Attitudes, and Actions, Stunting